Structural and optical properties of nitrogen doped ZnO films - Alves, E.
In this study we discuss the structural and optical properties of ZnO films doped with nitrogen, a potential p-type dopant. The films were deposited by magnetron sputtering using different conditions and substrates. The composition and structural properties of the films were studied combining X-ray diffraction (XRD), Rutherford backscattering (RBS), and heavy ion elastic recoil detection analysis (HI-ERDA). The results show an improvement of the quality of the films deposited on sapphire with increasing radio-frequency (RF) power with a preferentially growth along the c-axis. The ERDA analysis reveals the presence of H in the films and a homogeneous composition over the entire thickness. The photoluminescence of annealed samples evidences an improvement on the optical quality as identified by the well structured near band edge recombination.